A meta-synthesis on nursing students’ perception of problem-based learning - Daud, Azlina (IIUM Press, International Islamic University Malaysia, 2017)
Problem based learning is an option of the teaching methods. PBL has been introduce in the nursing education in the late sixties. Later, PBL has been adopted by many nursing schools to produce nursing graduates who can explore options, are articulate and have the capacity for developing appropriate strategies based on reflective decision making and competent to practice. A meta-synthesis on nursing students’ perception of problem-based learning, serves the best available evidences for preparing educational practice guidelines in nursing curriculum, informing decision making and identify areas for further research. Although some nursing programmes are not applying PBL as a teaching method, with these meta-analyses findings of this systematic review can help in revising the nursing curriculum. The changes in nursing curriculum, nurses will be outstanding problem solver, critical thinker and self directed in order to deliver safe and professional care for their patients. A meta-synthesis on nursing students’ perception of problem-based learning, shows a definite evidence of transferable skills developed through PBL process that increased students‟ performance in clinical practice. The book targets a broad audience ranging from undergraduate nursing students to graduate students, from nursing lecturers to nursing curriculum decision makers.